2021
DOI: 10.1557/s43578-021-00423-y
|View full text |Cite
|
Sign up to set email alerts
|

Collagen-derived peptide, DGEA, inhibits pro-inflammatory macrophages in biofunctional hydrogels

Abstract: Macrophages are innate immune cells that play important roles in wound healing. Particularly, M1 macrophages are considered pro‐inflammatory and promote initial phases of inflammation. Long-term exposure to inflammatory stimuli causes an increase in M1 macrophages, which contributes to chronic inflammation. Activated M1 macrophages have been shown to upregulate integrin α2β1 expression. To interfere with α2β1 binding, we designed a biofunctional hydrogel utilizing a collagen I-derived peptide, DGEA (Asp-Gly-Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Multiple groups have demonstrated that the collagen I-derived peptide, DGEA, which supports 𝛼2𝛽1 binding and increased CD206 expression, resulted in a large population of macrophages polarized towards a pro-reparative state. [26,56] Bi-or tetra-functionalized peptides are often used as chemical crosslinkers in HA hydrogels and synthetic scaffolds. While PEG-based crosslinkers are very common, peptide crosslinkers can be designed to allow dynamic remodeling of the matrix and proteolytic-based cell invasion.…”
Section: Designer Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple groups have demonstrated that the collagen I-derived peptide, DGEA, which supports 𝛼2𝛽1 binding and increased CD206 expression, resulted in a large population of macrophages polarized towards a pro-reparative state. [26,56] Bi-or tetra-functionalized peptides are often used as chemical crosslinkers in HA hydrogels and synthetic scaffolds. While PEG-based crosslinkers are very common, peptide crosslinkers can be designed to allow dynamic remodeling of the matrix and proteolytic-based cell invasion.…”
Section: Designer Hydrogelsmentioning
confidence: 99%
“…Multiple groups have demonstrated that the collagen I‐derived peptide, DGEA, which supports α2β1 binding and increased CD206 expression, resulted in a large population of macrophages polarized towards a pro‐reparative state. [ 26,56 ]…”
Section: Biomaterials Scaffolds Modulate Immune Cell Phenotypementioning
confidence: 99%
“…Material-and cell-based technologies designed for therapeutic transplantation hold enormous potential for treating diverse human diseases. Over the past several decades, a vast portfolio of such technologies has been developed 1 , including materials designed to support angiogenesis [2][3][4] , promote transplanted cell survival 5,6 or fate choice 7,8 , modulate the immune response 9,10 , capture malignant cells 11 , or deliver biological therapeutics 12,13 . More recently, numerous technologies composed of materials and cells, such as engineered tissues designed to replace or supplement the functions of highly metabolic tissues and organs, have been introduced 14 .…”
Section: Mainmentioning
confidence: 99%
“…Staatz et al [ 104 ] synthesised peptides to investigate the inhibition of platelet adhesion to collagen. It was shown that DGEA was the α2β1 recognition sequence [ 104 ] and that integrin-collagen interaction could be disrupted by the addition of DGEA peptides, providing evidence of the importance of this sequence in α2β1 integrin binding [ 107 , 108 ].…”
Section: Ecm-derived Peptide Sequences and Their Use In Biomimetic Hy...mentioning
confidence: 99%